Effect of Hydrothermal Temperature on the Structural, Morphological and Optical Properties of Tin Oxide Micro-Flowers - S. Beden, Ali; Moghaddam, Hossain M.; Samaneh R. Jamnani (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In the present study, we intend to evaluate the effect of temperature on the structural, morphological, and optical properties of tin oxide. For this purpose, tin oxide micro-flowers were prepared by the hydrothermal method at two different hydrothermal temperatures of 130 and 150°C. The synthesized samples were investigated and characterized using X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Ultraviolet–Visible Spectroscopy (UV-Vis). The XRD results showed that the synthesized samples have single-phase crystallinity with a rutile structure. The mean crystallite size for synthesized Micro- flowers was calculated by the Debby-Scherrer equation and the values were 21 and 28 nm for 130 and 150°C respectively. The results of FESEM showed the morphology of tin oxide is Micro-flower for both temperatures and increasing the temperature from 130 to 150°C caused the morphology of tin oxide samples to change from Micro-flowers consisting of nanoparticles to Micro-flowers consisting of nanoplates. The optical bandgap was increased, whereas the refractive index decreased by increasing temperature from 130 to 150°C.